Factors associated with overweight and obesity in Mexican school-age children: results from the National Nutrition Survey 1999 - Hernández Bernardo; Cuevas-Nasu Lucía; Shamah-Levy Teresa; Monterrubio Eric A; Ramírez-Silva Claudia Ivonne; García-Feregrino Raquel; Rivera Juan A; Sepúlveda-Amor Jaime (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: The objective of the study was to measure the prevalence of overweight and obesity in Mexican school-age children (5-11 years) in the National Nutrition Survey 1999 (NNS-1999). MATERIAL AND METHODS: Overweight and obesity (defined as an excess of adipose tissue in the body) were evaluated through the Body Mass Index (BMI) in 10,901 children, using the standard proposed by the International Obesity Task Force. Sociodemographic variables were obtained using a questionnaire administered to the children's mothers. RESULTS: The national prevalence of overweight and obesity was reported to be 19.5%. The highest prevalence figures were found in Mexico City (26.6%) and the North region (25.6%). When adjusting by region, rural or urban area, sex, maternal schooling, socioeconomic status, indigenous ethnicity and age, the highest prevalences of overweight and obesity were found among girls. The risks of overweight and obesity were positively associated with maternal schooling, children's age and socioeconomic status. CONCLUSIONS: Overweight and obesity are prevalent health problems in Mexican school-age children, particularly among girls, and positively associated with socioeconomic status, age, and maternal schooling. This is a major public health problem requiring preventive interventions to avoid future health consequences.